1986
DOI: 10.1149/1.2108519
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to the Design of Radiation‐Sensitive Polymeric Imaging Systems with Improved Sensitivity and Resolution

Abstract: In this paper the design of radiation sensitive polymeric imaging systems is reviewed. Advances in design have led to systems that function on the basis of radiation-induced changes in the polarity of polymer repeating units rather than cross-linking. These new systems offer improved resolution, since they do not swell during development. Improvement in sensitivity has been achieved by designing systems that incorporate chemical amplification. The design principles leading to amplification and examples of syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(66 citation statements)
references
References 14 publications
1
65
0
Order By: Relevance
“…The T c for the conventional polyphthalaldehyde is around -43 °C. Willson and Ito have reported the use of a KrF excimer laser, to irradiate polyphthalaldehyde without addition of photoacid generators, to yield clean, spontaneous "self-development" to the substrate [34]. We are seeking to investigate the properties of this polymer when exposed to 193 nm light.…”
Section: Polyphthalaldehydesmentioning
confidence: 99%
“…The T c for the conventional polyphthalaldehyde is around -43 °C. Willson and Ito have reported the use of a KrF excimer laser, to irradiate polyphthalaldehyde without addition of photoacid generators, to yield clean, spontaneous "self-development" to the substrate [34]. We are seeking to investigate the properties of this polymer when exposed to 193 nm light.…”
Section: Polyphthalaldehydesmentioning
confidence: 99%
“…18 Epoxide resins containing a PAG are routinely used for two-dimensional lithographic patterning. 19,20 Conventional ultraviolet (UV)-sensitive PAGs, such as diaryliodonium and triarylsulfonium cations, have been used for two-photon microfabrication. 21 However, the TPA cross-sections of these initiators are typically very small (δ ≤ 10 10 -50 cm 4 s photon -1 ), and as a result they exhibit low two-photon sensitivity.…”
Section: Design Of a Two-photon-activatable Photoacid Generatormentioning
confidence: 99%
“…Results of several reaction kinetics studies have been published to support the PEB modeling of CARs. Some of the early investigations on the reaction kinetics were performed by Willson [16], Fedynyshyn [17] and Reichmanis [18]. Seligson et al demonstrated that a reciprocity existed between the exposure dose, the bake temperature, and the bake time and expressed this reciprocity mathematically as an "effective dose" [19].…”
Section: Modeling the Post Exposure Bakementioning
confidence: 99%